Workplace risk Assessment Program for Advanced Technology Training Center (AdTec), Jerantut - K. A., Johari; Azizan, Ramli; Mohd Shaiful Zaidi, Mat Desa (Universiti Malaysia Pahang, 2019)
Advanced Technology Training Center, Jerantut or known as AdTec-Jerantut is one of the leading TVET institute in East Coast region. AdTec has 69 active staffs consist of technical (49 persons) and administrative staffs (20 persons). Since technical education deals with equipment and workshop/laboratory activities, safety and health risks due to hazardous conditions have become a leading concern and ask for an immediate mitigation strategy. This is because workshop and laboratory activities involve with a lot of physical movement and expose to certain safety and health risks such as dust, noise, electrical/mechanical (using of machines) and hazardous chemicals, to name a few. The main issue that requires an immediate attention here is most of the AdTec’s staffs are lacking of expertise with regards to workplace risk assessment technique. Some of them even not aware about these life-threating safety and health hazards and fail to foresee future effects of their daily activity at workshop and laboratory to their own safety and health. Moreover, this newly-established institute has inadequate information with regards to occupational safety and health hazards due to little exposure to such an information and lack of experience. Thus, the knowledge on hazard identification, precautionary measures and prevention strategies is very important for them in order to improve their workplace environment. Technical education and training involve practical and hands-on activities which require the trainers and trainees to be at the workshop and laboratories. This condition will expose them to all kind of potential hazards, especially when the hazards mitigation is not in place or less control. Sharing and transferring of knowledge and university’s expertise through this KTP-PSH program would be able to enhance and improve AdTec’s workplace environment, in particular their workshop and laboratories. This initiative and program will ultimately reduce the probability of accident occurrence. Moreover, this program is not only about equipping AdTec’s staffs with workplace risk assessment skill and technique but we will assist them to establish the internal reporting and monitoring system as well. This system indeed will allow their staffs and students to involve in workplace risk assessment and share the information within an internal cycle. Toward the end of this program, participants will understand how to conduct risk assessments for all activities in their organization and able to recommend the best solutions to address intolerable risks that exist. To date, the first cycle of the program has been conducted successfully whereby all the 17 participants have undergone the training and passed the assessment (written test and interview).